DIGITALISASI KAJIAN SANAD HADIS: TAKHRIJ DAN I’TIBAR SANAD DENGAN SOFTWARE GAWĀMI’ AL-KALĪM - Najiyah, Nur Laili Nabilah Nazahah; Hadi, Ahmad (Al-Bayan: Journal of Hadith Studies, 2023)
Hadith studies continues to experience renewal, especially in relation to the validation test of a hadith. Sanad is one of the validations that the hadith originates from the Prophet Muhammad saw. In this modern era, hadith applications began to emerge that contain similar things, one of which is Gawāmi' Al-Kalīm Software. This paper aims to describe the method of studying sanad hadith, especially the takhrij and I'tibar sanad methods through the Hadith software application Gawāmi' Al-Kalīm (V.4.5). This study answers two formulations of the problem, including: how the genealogy of takhrij and I'tibar sanad hadith; how it is applied using Gawāmi' Al-Kalīm hadith software. The data obtained in this qualitative research was sourced from several literature in the form of books, journals, theses / theses and official websites related to the theme of this research through three steps, namely data condensation, data presentation, and conclusion drawing / verification. As a result, the study of sanad hadith manually through the book is relatively long, so that the variety of hadith software, especially Gawāmi' Al-Kalīm v.4.5. Present to facilitate as well as minimize time in studying sanad hadith. One of the advantages is that there are various scholarly assessments of rawi hadith, as well as complete reference sources. However, one of the drawbacks, this software only provides Arabic as the main language of the program